Comparing Fall Food Plot Blends for Deer: 2006 Update - Rick Williams; Tim Baxley (EDIS)
FOR-113, a 5-page illustrated fact sheet by Rick Williams and Tim Baxley, describe the results of tests of forage species and mixtures for fall planting that are similar to those available to area sportsmen, evaluating forage production and nutritional quality. Includes references. Published by the UF School of Forest Resources and Conservation, December 2006.